Aplikasi Pemesanan Kursus Musik Pada Klinik Musik - Irafan Munthoriq; Emmy Wahyuningtyas; Noven Indra Prasetya (Informatics Engineering Department-UWKS, 2016)
Technology with speed, simplicity and security becomes a major consideration in developing or create new applications to increase productivity and customer satisfaction. It is to be applied to Clinic Music one of the music courses that provide music lessons private and non private in Surabaya.Music Clinic has a website which ranksfirst digoogle resulting music clinic has many visitorswho ask about music lessons at the Music Clinic, but the number of students who finally entered still few and far where other music courses. Therefore Clinic Music wants to improve services, especially services for students and prospective students who are different from other music courses. Facing the above problems researchers plan to create a mobile based application that is easy to use for students and prospective students are booking application music courses designed using the Waterfall method. In the application of prospective students can view information about the course in Clinical Music includes teaching, course packs and course program and can sign up and book a course schedule so that prospective students no longer need to come to the course. With this application, the applicant will be easier to register and book a course at the Music Clinic and can manage the schedule for the course